(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article describes non-standard ususes for solving trigonometric equations. It presents the method of sectors and the method of concentric circles from non-standard methods of solving trigonometric inequalities based on the principle of the genetic approach.